CULTURAL APPROACHES IN CYBERPORN CRIME PREVENTION - Prima Angkupi (Faculty of Law, Universitas Jenderal Soedirman, 2017)
Limitations of law in cyberporn law enforcement demands the need for non-penal approach as pre-ventive effort to eliminate causes of Cyberporn crimes. This approach includes crime prevention which aims to prevent a crime from being recurred. This approach can be implemented through situ-ational control by active involvement of cultural roles in community. However, it cannot be separat-ed from observing human life variations including childhood, youth, family, school, gender, peer group which play significant role during productive period. Those variations cane be taken as a theo-retical base for cyberporn crime prevention.Keywords: pornography, internet, crime prevention